Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.53620/pay.v1i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Liquid Organic Fertilizer (POC) from Household Waste in Gunung Elai Village

Abstract: Pengelolaan sampah terutama limbah rumah tangga merupakan permasalahan umum yang dialami masyarakat. Kurangnya pemahaman masyarakat tentang cara pembuatan Pupuk Organik Cair (POC) dari bahan organik berupa limbah  menjadi penyebab tidak terkelolanya limbah rumah tangga. Untuk itu, perlu dilakukan penyuluhan dan demonstrasi pembuatan Pupuk Organik Cair dengan memanfaatkan limbah rumah tangga di Kelurahan Gunung Elai. Pelatihan ini bertujuan untuk membantu masyarakat dalam mengelola limbah rumah tangga, serta me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…In this study, the addition of NASA POC was carried out as an additional supplement to the straw plus rice bran substrate. Liquid Organic Fertilizer (POC) containing N, P, K, and other minerals resulting from the decomposition of organic matter, is usually applied as a liquid fertilizer on plants (Mangera & Ekowati, 2022). The results of this study showed that the addition of NASA POC supplements up to 2 -3.5% on the substrate of straw plus rice bran had no significant effect on the growth of oyster mushroom mycelium in Baglog (LPM), the time required for pinhead emergence (AMP), pinhead number, diameter oyster mushroom hood, and weight of oyster mushroom.…”
Section: Oyster Mushroom Production (Pleurotus Ostreatus)mentioning
confidence: 99%
“…In this study, the addition of NASA POC was carried out as an additional supplement to the straw plus rice bran substrate. Liquid Organic Fertilizer (POC) containing N, P, K, and other minerals resulting from the decomposition of organic matter, is usually applied as a liquid fertilizer on plants (Mangera & Ekowati, 2022). The results of this study showed that the addition of NASA POC supplements up to 2 -3.5% on the substrate of straw plus rice bran had no significant effect on the growth of oyster mushroom mycelium in Baglog (LPM), the time required for pinhead emergence (AMP), pinhead number, diameter oyster mushroom hood, and weight of oyster mushroom.…”
Section: Oyster Mushroom Production (Pleurotus Ostreatus)mentioning
confidence: 99%
“…Masyarakat sangat antusias mengolah limbah organik perkotaan menjadi kompos dan pupuk organik cair (POC) untuk bertanam melon, bunga kol, tomat dan terong ( 1) . POC dari limbah rumah tangga mengandung N total 0,08%, P total 0,07%, K total 0,28%, 5 ppm total Fe, 0,4 ppm total Mn, 0,0 ppm total Cu, Zn total 0,6 ppm, total S 0,5%, total Ca 165,0 ppm, total Mg 106,9 ppm, total Na 172,7 ppm, C organik 1,06%, dan rasio C/N 13,27 (Mangera and Ekowati, 2022). Penggunaan POC merupakan terobosan yang telah dilakukan para peneliti dalam membantu budidaya melon (Aulia et al…”
Section: Introductionunclassified